Production Pectinases from Some Species of Aspergillus by Solid State Fermentation and Determination of Optimum Parameters for Production - Taowz, Rasha Ahmad; Faleh, Adib; Khateeb, Fateh; Alazm, Muhammad (Journal of agricultural, environmental and veterinary sciences, 2022)
After twenty Fungal isolates belong to Aspergillus Genus were obtained from sixty four samples from Fruits and Vegetables, and election the best according to its production Pectinases on solid medium. The strongest five isolates were chosen to product Pectinases by using solid state fermentation to know the ability of the elected isolates to produce pectinases, and determinate the highest enzyme production isolate, in addition to optimize the enzyme production for that isolate (incubation temperature, incubation period, pectin amount, inoculum volume, Suspension concentrations of spores, Carbon source, Nitrogen source). Four of these isolates were belong to Aspergillus niger and one of them were belong to Aspergillus fumigatus. Citrus peels were used in fermentation system as pectin resource. The pectin percentage in peels was calculated and it was 5%. The results showed that the activity of pectinases which was produced by isolates from citrus fruits is higher than the other isolates, and it was 51,52 U/ g. When the optimum parameters of production Pectinases were studied, the results showed that the highest activity of pectinases was obtained at 40°C of incubation temperature, 96 hours of incubation period, 2.5g of pectin amount in medium, 107 spore/ ml of spores concentration in fungal suspicion, 1.5 ml of indeed suspicion volume, using Citrus pectin as carbon sources, and Ammonium sulfate as nitrogen sources.